On Rationality of Kneading Determinants - Sheng Chen; Chao Xia (The Scientific World Journal)
In this section, R denotes a ring with identity I. We study conditions under which I−Aλ and I−Bλ are left coprime or right coprime, where A,B∈R. As applications, we get sufficient conditions under which the Kneading determinant of a finite rank pair of operators on an infinite dimensional space is rational.